Effects of training sets sequence on swimming performance, training load and physiological responses - Nikitakis, I. S.; Bogdanis, G. C.; Paradisis, G. P.; Toubekis, A. G. (Sports, 2023)
The study examined the effect of set sequence on performance and physiological responses in a training session and in each set separately. Twelve male swimmers performed four sessions in a randomized order, including a combination of two training sets: (i) set A-set C, (ii) set C-set A, (iii) set B-set C, (iv) set C-set B. Set A consisted of 8 × 200 m at a speed corresponding to lactate threshold (30 s recovery), set B included 8 × 100 m at the maximal aerobic speed (30 s recovery), set C included 8 × 50 m sprints at 95% of the maximum 50 m speed (30 s recovery). Speed, blood lactate, pH, base excess, bicarbonate and heart rate variability (HRV) were measured. Speed in each set was similar between sessions irrespective of set sequence (p > 0.05). Physiological responses during sets A and C were similar in all sessions (p > 0.05). In set B, when applied after set C, the metabolic response increased, and HRV decreased (p < 0.05). Overall, session biochemical disturbance was higher when set C was applied before sets A and B (p < 0.05). The magnitude of metabolic and HRV responses in a set conducted at maximal aerobic speed, but not at lactate threshold intensity, is increased when applied after sprint intervals.